Efeito antimicrobiano do óleo essencial de Ocimum carnosum em biofilme duo-espécie de Candida albicans e Streptococcus mutans sobre espécimes resina acrílica - Lima, Marcella Maria Rocha (2019)
Biofilms are complex communities that may involve different species of microorganisms, such as bacteria and fungi. These microorganisms can be found in Oral Total Prosthesis (PTs). Biofilm can lead to prosthetic stomatitis, which is a condition characterized by widespread inflammation of the mucosa covered by the prosthesis surface. Cleaning means are indicated to prevent the formation of oral biofilm, the most common are chemical methods. However, these compounds may cause mucosal irritation or affect the physical properties of prosthesis. There is interest in herbal medicines that have antimicrobial activity and are biocompatible to human tissues, such as Ocimum carnosum essential oil (OEOC), popularly known as Alfavaca-do-mato. The objective of the study was to evaluate the antimicrobial effect by using a formulation containing Ocimum carnosum essential oil in biofilm of Candida albicans and Streptococcus mutans duo formed on acrylic resin specimens. The OEOC was collected from dried leaves and extracted by the steam drag technique. The concentration of the formulation was previously determined by the Minimum Inhibitory Concentration (MIC). For MIC determination, OEOC was tested at 32% to 0.015% dilutions in a 96-well plate containing 100 μl Brain Heart Infusion - BHI medium, 5 μl of each strain of Candida albicans and Streptococcus mutans and 100 μl of the formulation tested. Control groups were tested with the formulation diluent as positive control and 0.12% chlorhexidine digluconate as negative control. A concentration of 4% of the formulation for use was obtained as a result. Microbiological analysis was performed using the same MIC strains that also underwent activation and inoculation using Brain Heart Infusion Broth (BHI) for C. albincans and BHI supplemented with glucose for S. mutans. The strains were adjusted on the McFarland scale. Specimens made with self-curing acrylic resin (10 mm diameter x 5 mm high) were randomly assigned to biofilm formation, divided into 3 technical triplicates and 3 biological triplicates: 4% OEOC; 0.12% Chlorhexidine Digluconate (CLX) and Formulation Diluent (DIL), each group being left for 1 hour and 3 hours soaking in a 24-well plate plus BHI sucrose supplemented broth and 18.75 μl of each strain. The specimens were washed with 0.89% saline solution after 24 hours and the medium was changed. After 24 hours of biofilm growth, the specimens were transferred to sonicated microfuge tubes, diluted to a concentration of 10-7 and seeded in 10 μl petri dishes each drop. After incubation in the greenhouse at 37 ± 1 ºC, 5% CO2 of 48 hours, the results were obtained in colony forming units (CFU) per ml / mg, using the values obtained through the dry weight of the biofilm formed at the end of the experiment. Data were tabulated and subjected to the Shapiro Wilk normality test, followed by two-way ANOVA and a Tukey post-test (p <0.05) using the SigmaPlot 11.0 program. The results showed that, for C. albicans strain, the OEOC was statistically similar to CLX (p> 0.05) for the 1 hour immersion interval, and for S. mutans, the drug was statistically superior. (p> 0.05) when compared to the efficacy of the CLX groups and formulation diluent for the 3 hour interval. Thus, it appears that OEOC has antimicrobial effect on Candida albicans and Streptococcus mutans and may, through further studies, be viable in the use of prosthesis disinfection.